Rancang Bangun Sistem Cerdas Pengontrolan Keamanan Kunci Kontak dan Pelacakan Pada Sepeda Motor Berbasis IOT - sulistyo, eko; Santrila, Hafizra; Haikel, M. Zuhriyandi; Ocsirendi, Ocsirendi (Manutech : Jurnal Teknologi Manufaktur, 2024)
The ignition key security system and motorcycle tracking are very important features that a motorcycle must have to secure the motorcycle from theft. The problem that occurs is that the key security system on motorbikes currently uses keyless and can only control one motorcycle and is not equipped with a tracking system, making it difficult for users to track the location of the motorcycle during theft. Therefore, this research will develop an ignition lock security system using keyless through an intelligent system application on android and equipped with a password to turn on or off more than one motorcycle to make it more efficient and cost-effective. While the tracking system is an additional feature developed in this research to track the whereabouts of motorbikes via android based on the location point and coordinates. The research method used in the ignition lock security system is to connect a 2-channel relay to the motorcycle electricity through NodeMCU which will control it through the application. Meanwhile, the tracking system uses the Neo-6M GPS Module to track the coordinates of the motorcycle location via GPS satellites. The results of the tracking are then sent to firebase to be processed into a motorcycle location point on the smartphone application. The test results show that the application can turn off and turn on more than one motorcycle using different passwords through the application on a smartphone and can display the location point of the motorcycle with a very small coordinate difference between the application and google maps so that it is considered to have a percentage error of 0%.